Association between fatty acid intake and age-related macular degeneration: a meta-analysis - Lee, Yan; Lee, Lok; Zhang, Li; Zhou, Qing (Frontiers in Nutrition, 2024)
Objective: The association of age-related macular degeneration (AMD) with the high and low fatty acids (FAs) intake, respectively, remains controversial. To this end, we performed a comprehensive meta-analysis of all the existing studies on the association of various intake levels of FA subtypes with AMD to determine these associations. Methods: A systematic search of PubMed, Web of Science, Cochrane Library and EMBASE was conducted through September 2023. To compare the highest and lowest groups, odds ratio (OR) with 95% confidence intervals (CIs) was analyzed with a random effects model/fixed effects model. Results: High intake of Omega-3 LCPUFAs (OR:0.67; 95%CI:[0.51, 0.88]; P=0.004), DHA (OR:0.80; 95%CI:[0.70, 0.90]; P<0.001), EPA (OR:0.91; 95%CI:[0.86,0.97]; P=0.004), and simultaneous intake of DHA and EPA (OR:0.79; 95%CI:[0.67, 0.93]; P=0.035) significantly reduced the risk of overall AMD. Conversely, a high intake of trans-FAs (OR:2.05; 95%CI:[1.29, 3.25]; P=0.002) was significantly related to an increased risk of advanced AMD compared with the low-intake group. Subgroup analysis results are shown in the articles. Conclusions: Increasing dietary intake of Omega-3 LCPUFAs, DHA, EPA, or simultaneous intake of DHA and EPA has a significant association with reduced risk of overall AMD. Various subtypes of Omega-3 also have a significant association with reduced risk of different stages of AMD. High intake of TFAs is significantly and positively correlated with the risk of advanced AMD. This could further support the idea that consuming foods rich in omega-3 LCPUFAs and reducing consumption of foods rich in TFAs may prevent AMD.